Pygmalion Effect: Esensi Ekspektasi Positif terhadap Keberhasilan - Maria Jenah; Ivana Destya Treeocta Fernandez; Novia Sumarni; Masduki Asbari; Salsabilla Agusna; Novi Ramayanti (Yayasan Aya Sophia Indonesia, 2023)
This study aims to determine the impact of the Pygmalion effect and its application in everyday life. This research is qualitative with a descriptive approach which is carried out using the note-taking method. The data source for this research is a video on the YouTube channel (Berilmu, 2022) entitled